Where blackbirds fly : a novel - Ray, Shann (University of Nebraska Press, 2025)
"A novel in five novellas, Where Blackbirds Fly offers a prismatic deep dive into the human heart through fierce narratives of intimacy both lovely and heartbreaking. Countering social upheavals, Shann Ray affirms the power of empathy, the wisdom of wilderness, and the felt presence of divine mystery echoed in the recurring appearances of blackbirds, as if etching flight patterns of mercy over the landscapes of human life. John Sender and Samantha Valeria Arrarás seek love in the financial industry, their initial attraction leading to unforeseen perils that will echo in those who enter and exit their lives. The characters of this novel form a compelling cross section of humanity met with revelation, suffering, and possibility. With spare and muscular prose, luminosity, and psychological grace, Ray weaves a tapestry as multihued as America in a vision of love's transgressive power."--